La implementación de la nueva propuesta curricular de la carrera de educación inicial: el caso de la asignatura comunicación oral y escrita - Ulloa Toscano, María José (2017)
The present research aims to know the teaching process of the subject of Oral and Written Communication of group one of the career of Initial Education in the Polytechnic University Salesiana Quito-Campus Girón. The theoretical basis is developed according to the theme related to the problem presented in the present case study, having as fundamental orientation the teachinglearning process, based on documents such as: The curricular proposal of Initial Education, the Ten Year Education Plan Of Ecuador, the National Plan of Good Life and the documents presented by the ESC. This research work has a qualitative approach that allows the collection of data on the pedagogical practice of the Initial Education career, which seeks to detect possible conflicts that may hinder the proper development of the teaching learning process, field journals, interviews and surveys that Have allowed the collection of relevant information from the pedagogical practice in order to verify the degree of compliance with the guidelines proposed by the curricular proposal of Initial Education. Through the analysis of the accumulated information, conclusions have been obtained that contribute to the reflection on the pedagogical practice with the purpose of contributing in the improvement of the teaching-learning process of the Initial Education career..